Nanoporous Organic Polymer/Cage Composite Membranes1. Issue 4 (6th December 2012) - Bushell, Alexandra F.; Budd, Peter M.; Attfield, Martin P.; Jones, James T. A.; Hasell, Tom; Cooper, Andrew I.; Bernardo, Paola; Bazzarelli, Fabio; Clarizia, Gabriele; Jansen, Johannes C.
<x xml:space="preserve">Abstract</x> Organic–organic composite membranes are prepared by in situ crystallization of cage molecules in a polymer of intrinsic microporosity. This allows a direct one‐step route to mixed‐matrix membranes, starting with a homogeneous molecular solution. Extremely high gas permeabilities are achieved, even after ageing for more than a year, coupled with good selectivity for applications such as CO2 recovery.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>